Investigation of the most suitable location of insulation applying on building roof from maximum load levelling point of view - Ozel, M.; Pihtili, K. (Pergamon-Elsevier Science Ltd, 2007)
In this study, the maximum load levelling of periodic heat flux entering a room through a composite roof consisting of different insulation layer has been evaluated for different insulation positions in the roof. A numerical model based on implicit finite difference scheme was applied for 12 different roof configurations during typical winter and summer days. For this purpose, total insulation thickness was kept constant and insulation was placed as equally two pieces and as equally three pieces in different locations within the roof thickness. Then, insulation layers were moved I cm at a time across the roof thickness for 12 different configurations. Maximum and minimum values of periodic heat fluxes for each sweeping process in the roof were calculated for achieving the maximum levelling of the heat flux entering through the roof. It was found that the best load levelling was achieved in the case where three pieces insulation of equal thickness were placed one at the outdoor surface of the roof, the second piece of insulation was placed in the middle of the roof and third piece of insulation was placed at the indoor surface of the roof. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: building roof; insulation layers; maximum load levelling